Meta-analysis, decision analysis, and cost-effectiveness analysis methods for quantitative synthesis in medicine - Petitti, Diana B. (New York ; Oxford : Oxford University Press, 2000)
In this 2nd edition Petitti has added new material on cumulative meta-analysis and the exploration of heterogeneity, incorporated recommendations for standardizing the conduct of cost-effectiveness analysis, and updated the rest of the text.
Previous ed.: 1994.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Medicine -- Decision making; Statistical decision; Meta-analysis.; Cost effectiveness